Conflict Management and Resolution: Can We Agree? - Meredith Taylor (EDIS, 2019)
In a successful marriage, couples have more positive than negative interactions. There are more times of talking cheerfully than of talking angrily. Positive interactions and good times help couples feel loved and respected. Negative interactions and bad times lead to feelings of hurt, anger, and sadness. This document is FCS2181, one of a series of five publications that are part of Before You Tie the Knot, a marriage preparation curriculum of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date November 1, 2001. Revised November 2, 2005.